Pengaruh Modal Terhadap Pendapatan Pedagang (Studi kasus: Pasar Angso Duo Kota Jambi) - Sudirman Sudirman; Ubaidillah Ubaidillah (Universitas Batanghari Jambi, 2020)
research aims to find out the effect of variable capital on the income of traders in Angso Duo Market Jambi City. The study used primary data by disseminating qusioners to 92 respondents. The method used in this study is a simple linear regression method. while econoetry analysis using a simple linear regression model is carried out to identify the variables that affect. Variables used are capital variables as free variables and income variables as bound variables. The results of the analysis showed that the capital had a positive effect on the earnings of Angso Duo Market traders. This means that if the market trader increases his capital, then the income of the market trader will also increase.